Produção do cuidado em saúde e o serviço social - Silva, Alaide Maria Morita Fernandes da (2013)
The objective of this research was to analyze the relationship between social work and health care production, a challenge faced by health professionals during the operationalization of the Single Basic Health System s principles and guidelines. To do so, the following problem was posed: what is the relationship between social work and health care production in the teaching and working contexts in the city of Londrina? This research also searched for health care conceptions and meanings among research subjects; identified and analyzed how subjects built their knowledge on the theme; learned how each area sees their contribution to care production; analyzed the type of care produced by the social worker; and verified the necessary professional preparation and knowledge for health care in the work and teaching contexts. This qualitative research also looked for the contribution of those who, through teaching and/or their work, could play a relevant role towards meeting these goals. Research subjects were representatives of two groups: the first included twelve professors (nucleus and field tutors) from the Family and Health Multi-professional Residency and one coordinator from the Single Basic Health Unit (field preceptor); and the second by seven social workers from the public health system. Data were produced through documental research, participant observations and group discussions, being those collected from nineteen subjects carried out through group discussions during specific meetings scheduled for the two segments. The analysis was conducted based on the convergence of contents and themes which made possible their organization in the following categories: health care conceptions; health care professional preparation; areas contributions to health care production; social work and care actions in the vision of social work practitioners. As a result, it is possible to say that social work is intrinsically related to health care, understood as a human valuing process that searches for giving subjects more autonomy when facing factors that lead to suffering, considering them co-participants in this process. Caring, one way or another is part of the social worker practice and, while one of the care managers in the work team can articulate dimensions not always valued or possible of being incorporated by other professional to the act of care, they may be indispensable to it. Finally, it is considered that the ethics sense, which is part of human nature, can establish a relationship with the social work s own nature, turning care practices in the fields of services providing, social assistance policies and protective policies into a quality related to the constitution of the profession